2016
DOI: 10.1111/hdi.12452
|View full text |Cite
|
Sign up to set email alerts
|

Low versus high dialysate calcium concentration in alternate night nocturnal hemodialysis: A randomized controlled trial

Abstract: Although dialysate calcium prescription influenced biochemical parameters it was not associated with difference in progression of VC between HC and LC groups. An important finding was the potential impact of alternate night NHD in attenuating progression of VC and inducing stabilisation of LVMI and PWV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Consensus is lacking on the optimal dialysate calcium concentration, although high calcium dialysate may contribute to vascular calcification and aortic stiffness 41, 42, 43, 44, 45, 46, 47. Based on moderate quality of evidence, our findings strongly support use of low calcium dialysate to reduce aortic stiffness in ESRD.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Consensus is lacking on the optimal dialysate calcium concentration, although high calcium dialysate may contribute to vascular calcification and aortic stiffness 41, 42, 43, 44, 45, 46, 47. Based on moderate quality of evidence, our findings strongly support use of low calcium dialysate to reduce aortic stiffness in ESRD.…”
Section: Discussionmentioning
confidence: 64%
“… 42 Parallel RCTUnclear risk biasfLow calcium (1.12 mmol/l)( n = 14)High calcium (1.37 mmol/l)( n = 13)68 ± 12;66 ± 1366 ± 4;6 ± 4Masterson et al. 43 Parallel RCTUnclear risk biasfLow calcium (1.3 mmol/l)( n = 22)High calcium (1.6 or 1.75 mmol/l)( n = 20)53 ± 21;48 ± 111225 ± 29g;16 ± 18gMarchais et al. 44 Parallel RCTHigh risk biasfLow calcium (1.50 mmol/l)( n = 13)High calcium (1.75 mmol/l)( n = 13)Not reportedSingle dialysisNot reportedMoor et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term use of HCD with a Ca 2+ ion concentration of 1.5 or 1.75 mmol/L promotes a positive Ca 2+ balance; however, long-term use of HCD increases the risk of vascular calcification in patients 8 , 10 . Studies have suggested that long-term use of dialysate containing 1.25 mmol/L Ca 2+ can effectively reduce the risk of cardiovascular calcification in MHD patients 11 13 , but it may also increase the risk of hypotension, muscle twitching, arrhythmias, and even sudden cardiac death in patients during dialysis 14 16 .…”
Section: Discussionmentioning
confidence: 99%